Translucent beads, shinier worlds: a preliminary approach to fluorite beads from the Iberian Peninsula - Lloret, C. P. Odriozola (2019)
Prehistoric ornaments are considered as aesthetic categories that show, emphasize and materialize codes, metaphors and narratives socially shared (Bar-Yosef Mayer and Porat 2008; DeMarrais et al. 1996; Hodder 1982; Tilley 1999; Wright and Garrard, 2003). Some values and properties as colour (Jones and MacGregor, 2002; Sahlins, 1976), but also brightness (Gaydarska y Chapman, 2008), have been highlighted as determinant of cultural/symbolic and technological choices in Prehistoric materiality, conditionating the raw material selection. Transparent and translucent minerals are considered for the Neolithic onwards as rare and highly symbolic elements. This paper shows that translucent beads accounts for an ample variety of raw material (i.e., calcite, muscovite, quartz varieties…). Fluorite (CaF2) occurs worldwide, and it´s relatively frequent in western Europe, and the Iberian Peninsula. Its properties (4 hardness in Mohs´ Scale) made it easy to worked out and cleavage for making ornaments. Some Belgium´s Upper Palaeolithic sites gave important evidences of its use (Goemaere et al., 2013; Jungels and Goemaere, 2007) and French and Belgian Neolithic and Copper Age communities used fluorite as a rare raw material for personal ornaments.